2023
DOI: 10.1038/s41467-023-40472-x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes jasmonate-mediated defense against nematodes

Abstract: Autophagy, as an intracellular degradation system, plays a critical role in plant immunity. However, the involvement of autophagy in the plant immune system and its function in plant nematode resistance are largely unknown. Here, we show that root-knot nematode (RKN; Meloidogyne incognita) infection induces autophagy in tomato (Solanum lycopersicum) and different atg mutants exhibit high sensitivity to RKNs. The jasmonate (JA) signaling negative regulators JASMONATE-ASSOCIATED MYC2-LIKE 1 (JAM1), JAM2 and JAM3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In line with the procedures described by a previous study [ 54 ], GUS histochemical staining and luciferase (LUC) was employed to detect the interaction between transcription factors and promoters. The binding site repeated three times in series was used as promoter sequence.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the procedures described by a previous study [ 54 ], GUS histochemical staining and luciferase (LUC) was employed to detect the interaction between transcription factors and promoters. The binding site repeated three times in series was used as promoter sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, as the housekeeping mechanism of eukaryotes, autophagy can degrade macromolecular protein aggregates and organelles, playing a crucial role in nutrient cycling, cellular waste management, and organelle quality control [ 29 , 32 ]. The double-membrane structure of autophagosomes is formed in the cytosol and can engulf intracellular components and transfer to vacuoles for further degradation and reuse [ 33–35 ]. Previous studies have shown that autophagy is involved in regulation of tapetal cells degradation and pollen development [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%